Influence of typical handball characteristics on upper body posture and postural control in male handball players - D. Ohlendorf; S. Salzer; R. Haensel; J. Rey; L. Maltry; F. Holzgreve; J. Lampe; E. M. Wanke; D. A. Groneberg (BMC, 2020)
Abstract Background Well defined constitutional parameters support the physical fatigue resistance in handball to maintain the performance level for the majority of actions. Ideal constitutional conditions are necessary to achieve these physiological advantages in handball. But limited knowledge exists about the upper body posture or the postural control in correlation to the Body Mass Index (BMI), playing years, playing position and throwing arm in professional male handball. Methods Ninety-one male handball players participate (24.1 ± 5.9 years; playing experience 16.6 ± 5.7 years). A three-dimensional back scanner and a pressure measuring plate were used. Results Correlations between BMI and upper body posture and postural control were not significant. Same counts for the comparison between the left and right throwing arm according to upper body posture and postural control (p ≥ 0.05). Correlations between the years of playing can be found at pelvis height (p ≤ 0.04) and for the length of the Center of Pressure (CoP) (p ≤ 0.01). Wing players are 6.5-8.5 cm smaller. The playing position is independently of BMI, age or upper body posture (p ≥ 0.05). Backcourt players have a higher load of the left and a lower load of the right foot compared to wing players (p ≤ 0.001). Left-right comparison (p ≤ 0.001/ 0.01) can be seen in pivot player (covered area), backcourt player (weight distribution left/right [rear] foot), wing player (weight and force distribution left/right foot, covered area). Conclusion Goalkeeper, Backcourt and pivot players are taller and heavier than wing players. These physiological demands are not detectable in the upper body posture and slightly in postural control. Wing players have the most asymmetric load distribution and the longest length of CoP. Since goalkeepers do not differ from pivot or backcourt players, this can be lead back to the same training.